Influence of Profitability, Investment Opportunity Set (Ios) Leverage and Dividend Policy on Firm Value in The L Service in Indonesia Stock Exchange - Khuzaini Khuzaini; Dwi Wahyu Artiningsih; Lina Paulina (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
This research was aimed to analyze the significant influence of profitability, investment opportunity set (ios), leverage and dividend policy partially or simultaneously on firm value. The sample used in this research was Industrial Services in Indonesia Stock Exchange period 2013 to 2015 as many as 28 companies taken by using purposive sampling technique. Hypothesis testing of research using multiple linear regression analysis by SPSS 21 for windows programs. This research found that: (1) profitability has significant influence partially  on firm value; (2) investment opportunity set (ios) has significant influence partially  on firm value; (3) leverage has no significant influence partially  on firm value; (3) the dividend policy has no significant influence partially  on firm value; (5) profitability, investment opportunity set (ios), leverage and dividend policy have significant influence simultaneously on firm value with influence value of 46.7%.